THE IDENTITY OF HORNERA Jungh. (Thymeleaceae) - A. J. G. H. KOSTERMANS (REINWARDTIA, 1965)
Dr. Airy Shaw (Van Steenis, Fl. Males. Ser. I, 6(1): 48. 1960),referred Hornera Jungh.(Tijdschr. natuurl. Geschied. & Physiol. 7: 314. 1840) ten-tatively to Lauraceae.Hornera was described in an article with the misleading title: Nova genera et species plantarum Javanicum, as the species numbered 22 to 27 are from Japan. Under no. 22 there is a remark: "siccatam e regius japonico accepi".Flora Malesiana gives no clue where this Japanese collection came from; no collecting localities and no collectors are mentioned by Junghuhn).According to Maximowicz (in Bentham & Hooker f., Gen. PI. 3: 188-189. 1880) the genus should not be Japanese; this wrong statement is apparently due to the fact, that Maximowicz could not attribute the genus in its circumscription to any Japanese plant.